Cytogenetics of the small-sized fish, Copeina guttata (Characiformes, Lebiasinidae): Novel insights into the karyotype differentiation of the family - Toma, Gustavo Akira; de Moraes, Renata Luiza Rosa; Sassi, Francisco de Menezes Cavalcante; Bertollo, Luiz Antonio Carlos; de Oliveira, Ezequiel Aguiar; Rab, Petr; Sember, Alexandr; Liehr, Thomas; Hatanaka, Terumi; Viana, Patrik Ferreira; Marinho, Manoela Maria Ferreira; Feldberg, Eliana; et al. (PloS one, 2019)
Lebiasinidae is a small fish family composed by miniature to small-sized fishes with few cytogenetic data (most of them limited to descriptions of diploid chromosome numbers), thus preventing any evolutionary comparative studies at the chromosomal level. In the present study, we are providing, the first cytogenetic data for the red spotted tetra, Copeina guttata, including the standard karyotype, C-banding, repetitive DNA mapping by fluorescence in situ hybridization (FISH) and comparative genomic hybridization (CGH), providing chromosomal patterns and novel insights into the karyotype differentiation of the family. Males and females share diploid chromosome number 2n = 42 and karyotype composed of 2 metacentric (m), 4 submetacentric (sm) and 36 subtelocentric to acrocentric (st-a) chromosomes. Blocks of constitutive heterochromatin were observed in the centromeric and interstitial regions of several chromosomes, in addition to a remarkably large distal block, heteromorphic in size, which fully corresponded with the 18S rDNA sites in the fourth chromosomal pair. This overlap was confirmed by 5S/18S rDNA dual-color FISH. On the other hand, 5S rDNA clusters were situated in the long and short arms of the 2nd and 15th pairs, respectively. No sex-linked karyotype differences were revealed by male/female CGH experiments. The genomic probes from other two lebiasinid species, Lebiasina melanoguttata and Pyrrhulina brevis, showed positive hybridization signals only in the NOR region in the genome of C. guttata. We demonstrated that karyotype diversification in lebiasinids was accompanied by a series of structural and numeric chromosome rearrangements of different types, including particularly fusions and fissions.
Keywords: Evolution, Molecular; molekulární evoluce; karyotyp; Characiformes; Chromosomes; Female; RNA ribozomální; Animals; ženské pohlaví; mužské pohlaví; Karyotype; Male; Phylogeny; zvířata; fylogeneze; RNA, Ribosomal; chromozomy